Qualidade de vida, dor e incapacidade funcional de idosos com lombalgia agudizada: análise dos dados do estudo BACE - Carlos Vinícius de Barros (2014)
The Health Related Quality of Life (HRQoL) evaluation is essential in elderlies with worsened low back pain (LBP). The phenomena such as the population aging and feminization of the elderly arouse doubts about the elderly health facing the fact of their larger participation in the population. Therefore, the conditions that were previously young populations features have become prevalent among the elderlies. The worsened low back pain can be described in accordance of the pain intensity, the Disability, symptoms presence of pain irradiation to lower limbs (MMII) and prior history of back pain. This research aimed to analyze the studys data of Back Complaints in the Elderly (BACE) referring to the clinics characteristics of acute low back pain and the functional disability (Roland Morris Questionnaire - RDQ) in the elderly community and his influence on the awareness of the HRQoL using a generic instrument. The BACE study relates to a large study of the multicentric and longitudinal with the purpose of identifying the characteristics and the clinical course of the acute pain to the cronical pain on elderlies with low back pain living in countries as: Brazil, Australia and Netherland. The present study cut, in an observational transversal study drawing, a 302 elderlies sample provided from a database of BACE Brasil. The data selected were socio demographic, HRQoL (SF-36), depressive symptoms (CES-D), RDQ and the back pain characterization throughout the present pain intensity and with one week prior. The univariate analysis with the test t of student , detected significant statistic differences between elderlies with presence and absence of the irradiation on the domains of functional capability, physical aspects (PA), pain, social aspects, general state (GE) and vitality. Prior pain (low back pain in the past) showed statistics differences just in the PA domains, pain and GE (p<0,05). The correlation from Pearson between the functional performance, intensity of actual pain and prior pain And 8 domains Of the SF -36 were significant (p<0,05). The variable with the significant statistics differences in the test t and those variables that have some correlations also significant came in the linear regression models from type Stepwise to verify the how much ths variables explained the 8 domains from HRQoL from elderlies with low back pain. With the exception of the GS, the score of the RDQ influenced between 36% and 56% on the variation of the scores on the other domains of the HRQoL. The results of the present study demonstrate the functional incapability influence in the domains of the HRQoL from low back pain elderlies. These results indicate the importance of the physical evaluation parameters, functional capability and physical aspects, that can be modified, with important repercussions about the worsened low back pain elderlies life quality with similar features with the samples. In this context, the use of generic and specific instruments could facilitate the identification process of the compromised day activities in elderlies with low back pain and have help to the extent of clinical improvement and research interventions.